2021
DOI: 10.1038/s41598-021-84235-4
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine induced reproductive toxicity in male rats

Abstract: Although it is reported that olanzapine (OLZ), which is an atypical antipsychotic drug, causes sexual dysfunction in men, it is noteworthy that there is not any study evaluating the toxic effects of OLZ on the male reproductive system. In the scope of this research, it was aimed to assess the reproductive toxic effects of OLZ by oral administration of 2.5, 5, or 10 mg/kg of it to male rats for 28 days. For this purpose, sperm concentration, motility and morphology, and DNA damage were determined, and histopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 56 publications
(19 reference statements)
0
16
0
Order By: Relevance
“…adrenal glands and testes, as steroids can easily pass through the blood–brain barrier. For instance, olanzapine and to a lesser extent aripiprazole administration may directly decrease FSH, LH and testosterone levels and disturb spermatogenesis in male rats [ 24 ]. This effect may potentially be related with an inhibition of 3-βHSD activity in the Leydig cells.…”
Section: Resultsmentioning
confidence: 99%
“…adrenal glands and testes, as steroids can easily pass through the blood–brain barrier. For instance, olanzapine and to a lesser extent aripiprazole administration may directly decrease FSH, LH and testosterone levels and disturb spermatogenesis in male rats [ 24 ]. This effect may potentially be related with an inhibition of 3-βHSD activity in the Leydig cells.…”
Section: Resultsmentioning
confidence: 99%
“…The results of our current study show that clozapine, sertindole and ziprasidone caused changes in the seminiferous epithelium and affected stages of spermatogenesis. According to Ardiç and coworkers (2021) olanzapine also caused histopathological changes in rat testes [ 21 ]. The authors found disorganisation within seminiferous tubules (swelling of Leydig cells and intracytoplasmic vacuolisation of Sertoli’s cells in testicular parenchyma), exfoliation and degeneration of germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found disorganisation within seminiferous tubules (swelling of Leydig cells and intracytoplasmic vacuolisation of Sertoli’s cells in testicular parenchyma), exfoliation and degeneration of germ cells. Olanzapine affected sperm morphology but did not affect sperm motility [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unusual morphologies percent was established. Considerably, the cytoplasmic leftover of sperms was considered as an unusual morphology 24 . The abnormality is seen in the head, middle piece, and tail of spermatozoa was noticed and categorized accordingly.…”
Section: Sperm Morphologymentioning
confidence: 99%